The impact of elevated water nitrite concentration on physiology, growth and feed intake of African catfish Clarias gariepinus (Burchell 1822). (19th September 2013) - Roques, Jonathan A C; Schram, Edward; Spanings, Tom; van Schaik, Tirsa; Abbink, Wout; Boerrigter, Jeroen; de Vries, Pepijn; van de Vis, Hans; Flik, Gert
Abstract: The nitrite threshold concentration in rearing water of African catfish ( Clarias gariepinus ) was assessed. African catfish with an initial mean (SD) weight of 219.7 (57.8) g were exposed to an increasing range of water nitrite from 6 (Control) to 928 μM nitrite for 28 days. Mean (SD) plasma nitrite concentrations increased from 5.0 (3.6) to 32.5 (12.6) μM at 928 μM ambient nitrite. The increase in nitrite was accompanied by gradual increase in plasma nitrate from 41.6 (28.4) μM to 420.2 (106.4) μM. Haematocrit, haemoglobin, methemoglobin, plasma concentrations of cortisol, glucose, lactate, osmolality, gill morphology and branchial Na + /K + ‐ATPase activity were not affected. Feed intake, final weight, SGR, FCR and mortality were not affected. We advise not to exceed a water nitrite concentration of 43 μM (0.6 mg L −1 NO2 − ‐N) to prevent the risk of reduced growth and feed intake in African catfish aquaculture.